The driving effect of internal and external environment on green innovation strategy-The moderating role of top management's environmental awareness. Issue 3 (14th December 2018) - Cao, Hongjun; Chen, Zewen
Abstract : Purpose: Green innovation strategy is not only a new idea to achieve green development but also the inevitable choice for enterprises to upgrade. At present, the research on the driving forces of green innovation strategy mainly focus on direct impact of single factor, lacking the overall consideration of internal and external environment. At the same time, research on the contingency effect of top management's environmental awareness is scarce. This paper aims to explore how external environment pressures (policy pressures and market pressures) and internal environment driving force (innovation resources and innovation capability) make enterprises to choose green innovation strategy with moderating effect of top management's environmental awareness. Design/methodology/approach: Based on the sample of 216 enterprises, this paper explores the relationship between policy pressure, market pressure, innovation resources, innovation capability and the green innovation strategy with moderating effect of top management's environmental awareness from inside and outside driving angle. Findings: The results of the hierarchical regression model show, first, the driving effect of factors in the external environment. The coercive policy has an inverted U-shaped impact on the green innovation strategy. The incentive policy and the market pressure both have a significant positive impact on the green innovation strategy. Second, the driving effect of factors in the internal environment. The innovation capability has a significant positive impact on the green innovation strategy. The innovation resources have no significant impact on the green innovation strategy. Third, the moderating effect of top management's environmental awareness. The relationship between the green innovation strategy and the coercive policy is stronger when the top management's environmental awareness higher. The relationship between the green innovation strategy and the market pressure is stronger when the top management's environmental awareness higher. The relationship between the green innovation strategy and the innovation resources is stronger when the top management's environmental awareness higher. Otherwise, the relationship between the green innovation strategy and the innovation capability is weaker when the top management's environmental awareness higher. And there is no significant change about the relationship between the green innovation strategy and the incentive policy when the top management's environmental awareness higher. Originality/value: First, the authors have promoted the integrated research on the drivers of the enterprise's green innovation strategy. From the perspective of internal and external environment driving forces, this paper analyzes the key factors influencing the decision-making of the green innovation strategy. Second, the study has contributed to the strategic choice theory. This paper studies the driving mechanism of the green innovation strategy from a new perspective of the strategic choice theory.